Assessment of Diabetes Health Promotion Behaviors for Clients with Type 2 Diabetes Mellitus at Diabetic Center in Al-Diwaniya City (Medico Legal Update, 2021)
Background: Diabetes mellitus (DM) is a significant worldwide medical issue that causes high human,social, and financial expenses on nations at all pay levels. The constant hyperglycemia of diabetes is relatedto long-term damage, brokenness, and disappointment of different organs, particularly of the eyes, kidneys,nerves, heart, and blood vessels.Method: A descriptive correlational design is used in this study which aims to measure health-relatedexperiences and lifestyle behaviors for clients with type 2 diabetes for the period from (1st October 2019 to27th August 2020). The study included a convenience sample of 358 clients with type 2 diabetes mellituswho were recruited from Al-Diwaniya Teaching Hospital at Diabetes and Endocrine Center.Data were collected using a self-report study instrument that includes the socio-demographic sheet, thehealth profile, and the Type 2 Diabetes and Health Promotion Scale. The data were analyzed using StatisticalPackage for Social Sciences (SPSS) version 26 using the frequency, percent, arithmetic mean, standarddeviation, Pearson correlation, Independent-sample t-test, and one-way analysis of variance (ANOVA).The study results displayed that most of participants reported poor Physical Activity level (n = 266; 74.3%),more than two-fifth reported good Risk Reduction level (n = 148; 41.3%), less than two-fifth reportedgood Stress Management level (n = 134; 37.4%), less than two-fifth reported fair Healthy Diet level (n= 135; 37.7%), more than two-fifth reported good overall behavior (n = 193; 53.9%). Furthermore, thereare statistically significant inverse correlations between participants’ age and their Physical Activity, RiskReduction, Stress Management, Enjoying Life, and overall behavior.Conclusion: The researcher concluded that the younger the clients, the poorer the Physical Activity, RiskReduction, Stress Management, Enjoying Life, and overall behavior; the older the client, the better theHealth Responsibility; the better socioeconomic status, the better the Physical Activity, Risk Reduction,Stress Management, Enjoying Life, and overall behavior.